Relationship between construction performance evaluation and contractor characteristics in Japan - Yukiko Konno (Cogent Business & Management, 2018)
In recent years, in the bidding for public works, it has become increasingly necessary to select a contractor not only by price, but also by the construction quality. This study analyses the relationship between the performance evaluations of construction work on Japanese public works and contractor characteristics. A fixed-effects model and a panel regression model were used for the empirical analysis of data from Keishin, which is a pre-bid qualification review of public works and project performance-evaluation system after the completion of construction in Japan. The results indicate that variables such as years in business and net sales have a significantly positive influence on construction performance. An important aim of national and local governments is to find contractors that carry out high-quality construction, and the results of this study can contribute to resolving this issue. In addition, the results highlight what resources and capabilities contractors should gather to improve their construction quality.
Keywords: 650